Accomplishing Difference: How Do Anti-race/Ethnicity Bias Homicides Compare to Average Homicides in the United States?. (19th September 2018) - Klein, Brent R.; Allison, Kayla
Abstract : Research on the nature of bias homicide has experienced increased interest in the academic literature. To date, few studies have compared the similarities and differences between anti-race/ethnicity bias homicides and average American homicides. Consequently, we know little about how the offender, victim, and situational characteristics compare across these two homicide types. Drawing from doing difference theory of bias crime, the aim of this study is to comparatively analyze the attributes of anti-race/ethnicity homicides to average homicides between 1990 and 2014. Anti-race/ethnicity homicide data is extracted from the U.S. Extremist Crime Database and paired with average homicides from the Federal Bureau of Investigation's 2000 Supplementary Homicide Reports. The results of this study suggest that the characteristics of anti-race/ethnicity homicides are both similar and different from average homicides. Implications for bias crime theory, research, and policy are discussed.